Upaya Penyelesaian Sengketa Pajak PT Taspen (Persero) Kantor Cabang Utama Medan - Pasca Putri Quitrine Purba; Dian Puji Simatupang (Jurnal Ilmiah Penegakan Hukum, 2023)
This article aims to find out how to resolve tax disputes between PT Taspen (Persero) and the Director General of Taxes of the Ministry of Finance regarding the amount of tax payable on Article 21 Income Tax (PPh) Employee Medical Expenses. The problem is focused on calculating the tax debt of PT Taspen (Persero) Medan Main Branch Office related to employee medical expenses. In order to approach this problem, theoretical references from state finances are used. This research is normative research by interpreting laws and regulations by judges by describing objects or events to get conclusions regarding the settlement of tax disputes. Based on the discussion of the analysis’ results of tax dispute resolution decisions for employee medical expenses, it can be concluded that inpatient and outpatient medical expenses are a deduction from employee income regarding taxable-deductible principle. Every income related to a job or any activity that is obtained by a personal taxpayer as long as the employer pays it and related to the job is an object of income. This study advise the management of PT Taspen (Persero) that it is not to pay for employees' medical expenses directly but using a third party, a health insurance company